2017
DOI: 10.5433/1679-0359.2017v38n4p2029
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestibility and nutritional characterization of distillers dried grains with solubles according to the Cornell Net Carbohydrate and Protein System

Abstract: We evaluated the fractions of protein and carbohydrates in distillers dried grains with solubles (DDGS), corn grain (CG), soybean meal (SM), and corn silage (CS), as well as the in vitro digestibility (IVD) of DDGS, CG, SM, CS, rations containing 0.0, 8.0, 16.0, and 24.0% DDGS, and in vitro fermentation parameters after 24 h of incubation. DDGS were obtained following microbial fermentation for ethanol production from a sugar and alcohol distillery located in the state of Mato Grosso -Brazil. The Cornell Net C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Previous research by Nuez-Ortín and Yu (2009), Salim et al (2010), and Geron et al (2017), among others, has shown that DDGS is usually composed of 87.0 -93.0% dry matter (DM), 28.1 -32.9% crude protein (CP), 8.2 -16.5% ethereal extract (EE), and 19.7 -4 9.5% neutral detergent fiber (NDF), and typically contains a total digestible nutrient (TDN) content in the 69.6 -78.5% range.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous research by Nuez-Ortín and Yu (2009), Salim et al (2010), and Geron et al (2017), among others, has shown that DDGS is usually composed of 87.0 -93.0% dry matter (DM), 28.1 -32.9% crude protein (CP), 8.2 -16.5% ethereal extract (EE), and 19.7 -4 9.5% neutral detergent fiber (NDF), and typically contains a total digestible nutrient (TDN) content in the 69.6 -78.5% range.…”
Section: Introductionmentioning
confidence: 92%
“…Ethanol is derived from the fermentation process, during which a byproduct called "distiller's dried grain solubles", or DDGS, is produced (RAUSCH;BELYEA, 2005;KIM;DALE, 2005). In Portuguese: "grão seco de destilaria com solúveis" -GSDS (GERON et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digestibility of DM, NDF and OM of the concentrates containing 50%, 75% and 100% RDDGS levels replacing SBM was higher (P<0.05) than concentrate mixture 1 (control) in the present study. However, Geron et al, (2017) reported no effect of inclusion of DDGS on IVDMD and IVOMD. Contrarily, Yogi et al (2017) showed that IVDMD decreased (P<0.01) after 50% inclusion of RDDGS replacing oil cakes, whereas IVOMD was unaffected except at 100% RDDGS where it was reduced.…”
Section: Nutrient Digestibilitymentioning
confidence: 98%
“…The bromatological composition of DDGS is as follows: 87.0% to 93.0% dry matter (DM); 28.1% to 32.9% crude protein (CP); 8.2% to 16.5% of ethereal extract (EE), 19.7% to 49.5% of neutral detergent fiber (NDF), and 69.6% to 78.0% of total digestible nutrients (TDN) (NUEZ-ORTÍN;YU, 2009;SALIM et al, 2010;GERON et al, 2017b). Studies are needed to determine appropriate levels of DDGS that could be included in ruminant rations (GERON et al, 2017a).According to Bremm et al (2008), the ingestive behavior of animals allows for the definition of adequate food management strategies, which 1269 Semina: Ciências Agrárias, Londrina, v. 39, n. 3, p. 1267-1280, maio/jun. 2018…”
mentioning
confidence: 99%